The Representation of the Loss of Faith in Matthew Arnold's Dover Beach - Harem Kareem Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The nineteenth century is largely recognized for the controversial disagreements between the newly scientific discoveries and religious theories. Thus, this paper presents data on the Victorian period and more specifically the poem Dover Beach by Matthew Arnold. Meantime, it highlights the loss of faith in the Victorian society of England through the lens of New Criticism and New Historicism theories. The research aimed at illustrating the loss of religion and the melancholic tone evoked by Matthew Arnold in his Well-known poem Dover Beach. At the beginning, it provides a critical insight on the principles and the histories of these two theories. Additionally, in the introduction, the paper contains significant information on the message of Dover Beach and its linkage to the theories. Equally important, follows it the discussion and analysis section, which is probably the fundamental part of the research. Finally, a brief conclusion is provided at the end.